PENYALAHGUNAAN QRIS DALAM TRANSAKSI ELEKTRONIK DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 2024 TENTANG PERUBAHAN KEDUA ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Stefanus Pattipeilohy; Indah Kusuma Wardhani (Constitutum: Jurnal Ilmiah Hukum, 2025)
QRIS is a national QR Code standard developed by Bank Indonesia and the Indonesian Payment System Association to facilitate easier, faster, and safer digital payment transactions. QRIS, as a form of electronic transaction, allows people to make payments using all QR Code-based payment applications, such as OVO, GoPay, LinkAja, and Dana. In practice, QRIS has a risk of misuse that will result in losses for its users. This study discusses the forms of QRIS misuse, the regulation of QRIS misuse based on Law Number 1 of 2024 concerning Electronic Information and Transactions, and efforts to overcome QRIS misuse. This study uses a normative juridical research method by examining secondary data. The results explain that the forms of QRIS misuse that often occur in society include QR Code forgery, falsification of transfer receipts, scamming, and phishing. Misuse of QRIS carried out by means of QR Code forgery and falsification of proof of transfer is a cyber crime regulated in Article 35 in connection with Article 51 paragraph (1) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions and misuse of QRIS carried out by means of scamming and phishing is a cyber crime regulated in Article 28 paragraph (1) in connection with Article 45A paragraph (1) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions. Efforts to overcome misuse of QRIS can be carried out through preventive measures and repressive measures.